Gerhard Tersteegen (1697-1769), Andrew Murray (1827-1917) en mistieke gnosis (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2024)
Andrew Murray’s interest in Tersteegen’s mystical work surfaced in numerous citations from Tersteegen’s publications and Murray’s fondness of reading Tersteegen’s poems. Particularly Tersteegen’s emphasis on losing oneself in God, being quiet in the presence of God, shutting out the rest of the world and true spiritual understanding in the inner chamber of the heart, appealed to Murray’s mystical inclinations. Tersteegen’s mystical profile reflects influences from a number of Medieval and post-Medieval sources. Mystical ideas from Origen, Augustine and Macurius, contributed in numerous respects to Tersteegen’s and Murray’s emphasis on spiritual understanding in the depths of the heart. Particularly Macurius’ metaphors of the bride’s (soul’s) longing for her Bridegroom (Jesus), the transcendental light of God in the heart and the metaphor of the heart as a tomb, in which the mind and its thoughts lie buried, until the deeper light of God shines in the deepest sanctuary of man’s being, surface prominently in Murray’s theology. Murray’s involvement with mystical gnosis gleaned from Tersteegen’s works, finds expression in his theological views that knowledge of God is life eternal and that abiding in Christ ensures fellowship with God in which the only true knowledge of God is to be have. Christ’s love, power and infinite glory may not be grasped through the human understanding, but the knowledge which is deeper than thoughts or words will be given the mystic soul ? the knowing of God, which comes of being known of Him.